Metal hyperaccumulation armors plants against disease. - Helen Fones; Calum A R Davis; Arantza Rico; Fang Fang; J Andrew C Smith; Gail M Preston (PLoS Pathogens)
Metal hyperaccumulation, in which plants store exceptional concentrations of metals in their shoots, is an unusual trait whose evolutionary and ecological significance has prompted extensive debate. Hyperaccumulator plants are usually found on metalliferous soils, and it has been proposed that hyperaccumulation provides a defense against herbivores and pathogens, an idea termed the 'elemental defense' hypothesis. We have investigated this hypothesis using the crucifer Thlaspi caerulescens, a hyperaccumulator of zinc, nickel, and cadmium, and the bacterial pathogen Pseudomonas syringae pv. maculicola (Psm). Using leaf inoculation assays, we have shown that hyperaccumulation of any of the three metals inhibits growth of Psm in planta. Metal concentrations in the bulk leaf and in the apoplast, through which the pathogen invades the leaf, were shown to be sufficient to account for the defensive effect by comparison with in vitro dose-response curves. Further, mutants of Psm with increased and decreased zinc tolerance created by transposon insertion had either enhanced or reduced ability, respectively, to grow in high-zinc plants, indicating that the metal affects the pathogen directly. Finally, we have shown that bacteria naturally colonizing T. caerulescens leaves at the site of a former lead-zinc mine have high zinc tolerance compared with bacteria isolated from non-accumulating plants, suggesting local adaptation to high metal. These results demonstrate that the disease resistance observed in metal-exposed T. caerulescens can be attributed to a direct effect of metal hyperaccumulation, which may thus be functionally analogous to the resistance conferred by antimicrobial metabolites in non-accumulating plants.